2022
DOI: 10.1001/jamanetworkopen.2021.42046
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Regional Variability in COVID-19 Outcomes Among Patients With Cancer in the United States

Abstract: IMPORTANCEThe COVID-19 pandemic has had a distinct spatiotemporal pattern in the United States. Patients with cancer are at higher risk of severe complications from COVID-19, but it is not well known whether COVID-19 outcomes in this patient population were associated with geography. OBJECTIVETo quantify spatiotemporal variation in COVID-19 outcomes among patients with cancer. DESIGN, SETTING, AND PARTICIPANTS This registry-based retrospective cohort study included patients with a historical diagnosis of invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…There may be residual confounding due to regional and center-level factors which are incompletely captured in the CCC19 data model. 30 Additionally, the exact timing of breakthrough infections in relation to COVID-19 vaccination were not precisely determined, as our current analysis relied on time intervals instead. Despite such limitations, this represents one of the largest cohorts with comprehensive clinical and biological data on vaccinated patients with cancer and breakthrough COVID-19 reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…There may be residual confounding due to regional and center-level factors which are incompletely captured in the CCC19 data model. 30 Additionally, the exact timing of breakthrough infections in relation to COVID-19 vaccination were not precisely determined, as our current analysis relied on time intervals instead. Despite such limitations, this represents one of the largest cohorts with comprehensive clinical and biological data on vaccinated patients with cancer and breakthrough COVID-19 reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the 31 included studies is presented in Table 1, and their primary and secondary outcomes are shown in Supplementary Table S2. Of the 31 included studies, 28 (90.3%) executed a cross-sectional study design based on secondary data analyses [26-30, 32-41, 43-45, 47-56], and 3 (9.7%) studies executed a retrospective cohort study design with longitudinal follow-up of patient outcomes [31,42,46].…”
Section: Resultsmentioning
confidence: 99%
“…Specific datasets included the Medicare Single Analytic Files [26,27,34,37,38,43,44,53], Medicare Provider Analysis and Review [36,56], SEER-21 [32], and the SEER-Medicare linked database [28,29,52]. Other specific national data sources included the National Center for Health Statistics [50], the CDC Wide-ranging ONline Data for Epidemiologic Research database [39], the COVID-19 and Cancer Consortium Database [42]. In addition, one study utilized data obtained from a national clinical trials database (ClinicalTrials.gov) [41].…”
Section: Patient Data Sourcesmentioning
confidence: 99%
“…7 Overall, mortality risk has decreased over time. 8,9 Risk factors for poor COVID-19 outcomes in patients with cancer have emerged, including male sex, being older than age 65, smoking status, a higher number of medical comorbidities, high Eastern Cooperative Oncology Group performance status, and the presence of hematologic malignancies or lung cancer, that are associated with disease severity, hospitalization, intensive care unit admission, and mortality.…”
Section: Covid-19 Outcomes In Patients With Cancermentioning
confidence: 99%